TIME DOMAIN EVALUATION OF MULTILEVEL CONVERTERS VOLTAGE AND CURRENT QUALITY - Urtanbayev, Nurlan (Nazarbayev University School of Engineering and Digital Sciences, 2016)
Multilevel converters are power conversion devices consisting of voltage sources and semiconductor switches. This work was motivated by the fact that majority of the conducted research estimates converter quality using frequency-domain approach, which is requires tones of calculation. As an alternative for frequency-domain approach, time-domain evaluation method, developed in a recent time, was selected. This method brings novelty in deep-seated method of convertor evaluation, based on frequency-domain. General goal of this thesis is to demonstrate competency and applicability of time-domain optimization method on online adaptive inverter systems. Work will be focused on development of algorithm for calculation of optimal parameters for single phase CHB converter. Modulation optimization and local minimum finding algorithms are developed and discussed in this work. Moreover, combination of SHE and THD minimization techniques was designed and simulated. Obtained results coincide with those presented so far. However, majority of the results are novel, and has not presented to community yet. Future work will focus on development of the optimization algorithm for three-phase inverters.
Keywords: Multilevel converters; convertor evaluation; CHB converter